Numerical computation of fluid–solid mixture flow using the SPH–VCPM–DEM method. (October 2021) - Ng, K.C.; Alexiadis, A.; Chen, Hailong; Sheu, T.W.H.
Abstract: In this paper, a unified particle-based solver is developed to solve complex fluid–solid​ mixture flow problem involving many elastic solid bodies. Our previous Fluid Structure Interaction (FSI) solver that incorporates Smoothed Particle Hydrodynamics (SPH) for fluid modelling and Volume Compensated Particle Method (VCPM) for elastic solid modelling is extended by incorporating the Discrete Element Method (DEM) for modelling the contact force between colliding elastic solid bodies. The contact force is modelled using the non-linear Hertzian formulation. The method is firstly validated by solving several benchmark FSI problems that involve only one solid body. Then, solid–solid interaction is modelled and the collision problem involving two elastic rings and the well-known Drafting, Kissing and Tumbling (DKT) phenomenon in a fluid domain are simulated. The results agree considerably well with other benchmark numerical solutions. The collapse of Aluminium cylinder layers (in dry and wet conditions) is then simulated and it is found that the numerical result is comparable to the experimental data. Following that, the SPH–VCPM–DEM method is used to solve a more complex problem involving the dumping of solid objects through solid and perforated fall pipes for scour protection. The results show the potential of the SPH–VCPM–DEM method in simulating complex fluid–solid mixture flow.